SISTEM INFORMASI RAPOR ONLINE PADA SMK PGRI GRAFIKA PAKIS MALANG BERBASIS WEB DAN SMS GATEWAY - Carina, Erin; Widayanti, Rahayu; Rahmawati, Linda Suvi (DINAMIKA DOTCOM, 2015)
SMK PGRI Grafika Pakis Malang a secondary education institution national scale which has two Program Preparation Skills Graphic and Graphic Production. Management of grades at SMK PGRI Grafika Pakis Malangtoday still use the conventional system to store student data. Processing of the results of the learning process using the Microsoft Excel application. The purpose of this research is to build web-based applications online report cards and sms gateway in SMK PGRI Grafika Pakis Malang. This study uses techniques of field research by conducting interviews in the academic and teacher in SMK PGRI Grafika Pakis Malang. Results of this research is an online information system report cards provide convenience academic field, especially teachers in processing the replay value, besides students / parents can receive information about academic online either through the internet or mobile phones and to produce information that is more precise, and accurate. Key words: Information Systems, Report Card, SMS Gateway